2018
DOI: 10.15847/obsobs12320181232
|View full text |Cite
|
Sign up to set email alerts
|

Las redes sociales de las organizaciones de marketing de destinos turísticos como posible fuente de eWOM

Abstract: ResumenEl turismo es uno de los sectores económicos de mayor crecimiento a nivel mundial; el de sol y playa, el principal de la industria turística española. Las redes sociales juegan un papel clave en el desarrollo de los destinos turísticos al ser uno de los canales principales para su difusión y comercialización, y un espacio para que los turistas reales y potenciales compartan sus experiencias influyendo en las decisiones de otros turistas. La presente investigación analiza la presencia y gestión de los pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
(60 reference statements)
0
8
0
5
Order By: Relevance
“…Finally, with regards to the features of tourist apps, the importance of their relational potential has been clearly established [1,2,31,44]. The selected apps do not exploit this capacity and the target public has not shown a particular interest in this possibility, however, we must insist on the desirability of promoting it and encouraging the conversion of this public into adprosumers by incentivizing their participation in virtual communities that are generated around tourist destinations [6,11,13]. It has been concluded that tourism must try to reach the largest possible number of age groups, including the elderly, by adapting its products and services to the needs of an increasingly older but eager and able to travel society [71].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, with regards to the features of tourist apps, the importance of their relational potential has been clearly established [1,2,31,44]. The selected apps do not exploit this capacity and the target public has not shown a particular interest in this possibility, however, we must insist on the desirability of promoting it and encouraging the conversion of this public into adprosumers by incentivizing their participation in virtual communities that are generated around tourist destinations [6,11,13]. It has been concluded that tourism must try to reach the largest possible number of age groups, including the elderly, by adapting its products and services to the needs of an increasingly older but eager and able to travel society [71].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of these mobile apps shows that they meet the expectations of senior tourists, who constitute a relevant generation for cultural tourism and are of special interest for the sustainability of WCHS. The configuration and development of these tools must be adapted to this generation, which we call Generation W.Sustainability 2019, 11, 3203 2 of 17 image and reputation of the destination [11,13]. Thus, RICT contribute to sustainable tourism through their communicational, relational, and experiential capacity [6,[14][15][16].…”
mentioning
confidence: 99%
See 3 more Smart Citations